Globalisation ghosts and the gatekeepers [Book Review] - Robie, D (Pacific Media Centre, 2011)
A review of the second edition of the book 'Dateline Earth: Journalism as if the Planet Mattered' by Kunda Dixit is presented. Dixit argues that his provocatively titled book encourages global journalists to be 'more attached' to the story on conflict, environment, development, poverty, deprivation or disaster. The reviewer suggests that the book was an inspiring, daunting and prophetic, insight into global journalism.
Keywords: Development journalism; Media education; Environmental journalism; Political journalism; Political economy; Citizen journalism